2018
DOI: 10.1177/0038040718762136
|View full text |Cite
|
Sign up to set email alerts
|

Falling Behind: Lingering Costs of the High School Transition for Youth Friendships and Grades

Abstract: This study investigates the influence of structural transitions to high school on adolescents’ friendship networks and academic grades from 6th through 12th grade, in a direct comparison of students who do and do not transition. We utilize data from 14,462 youth in 51 networks from 26 districts (Promoting School–Community Partnerships to Enhance Resilience). Results underscore the challenging nature of compulsory school changes. Students that structurally transition to high school between eighth and ninth grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 77 publications
0
58
1
Order By: Relevance
“…In another study in the US, Felmlee et al (, n = 14,462) found that pupils in through‐schools had better levels of educational and social outcomes compared to pupils who moved schools. However, Madjar et al ’s (, n = 128) study from Israel reported that children who were moving school had higher academic and social motivation compared to those who studied at through‐schools.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study in the US, Felmlee et al (, n = 14,462) found that pupils in through‐schools had better levels of educational and social outcomes compared to pupils who moved schools. However, Madjar et al ’s (, n = 128) study from Israel reported that children who were moving school had higher academic and social motivation compared to those who studied at through‐schools.…”
Section: Resultsmentioning
confidence: 98%
“…The impact of organisational models where pupils from one primary go to the secondary school and those where several primaries feed into one secondary have been compared. Although Langenkamp () reported that those pupils who moved to the latter model of secondary school had less chance of failing, Felmlee et al () reported that they faced a greater academic cost with this model to the extent that these effects could be seen throughout their secondary school career. Similarly, Temkin, Gest, Osgood, Feinberg and Moody () reported that transition from multiple feeder schools to one secondary school led to a decline in friendship stability and an increase in social distance between pupils.…”
Section: Resultsmentioning
confidence: 99%
“…An association between suspension and friendship discontinuity may also be a result of spuriousness rather than of an effect of the former on the latter. Friendship ties change year to year for many reasons, such as transferring schools (Felmlee, McMillan, Rodis, & Osgood, ), joining a sports team (Eder & Kinney, ), or engaging in certain behaviors. Some behaviors like substance use are associated with popularity or increases in friendship ties (Moody, Brynildsen, Osgood, Feinberg, & Gest, ), but others like delinquency and physical aggression are associated with fewer friends (Dodge, ; Rulison, Kreager, & Osgood, ) and increase risk of suspension.…”
Section: Introductionmentioning
confidence: 99%
“…An additional structural challenge is that when students transition to high school, they break social bonds with teachers and peers from middle school at the same time that they need to negotiate new social relationships, adapt to new school practices, and learn new school routines (Neild, 2009). Felmlee et al (2018) articulates that structurally transitioning into a new building for high school impacts adolescent friendship networks, which in turn impacts their ability to make a successful transition to high school. Students who made such a structural transition received fewer friendship nominations (had fewer friends), were more likely to become isolated, and had significantly lower odds of obtaining high grades (As and Bs), and that these outcomes persisted throughout high school (Felmlee et al, 2018).…”
Section: Structural Challengesmentioning
confidence: 99%
“…Felmlee et al (2018) articulates that structurally transitioning into a new building for high school impacts adolescent friendship networks, which in turn impacts their ability to make a successful transition to high school. Students who made such a structural transition received fewer friendship nominations (had fewer friends), were more likely to become isolated, and had significantly lower odds of obtaining high grades (As and Bs), and that these outcomes persisted throughout high school (Felmlee et al, 2018). Additionally, these two outcomes are positively correlated, suggesting that having fewer friends and dropping grades create a downward dynamic for students (Felmlee et al, 2018).…”
Section: Structural Challengesmentioning
confidence: 99%